PENGARUH KUALITAS LAYANAN INTERNET BANKING DAN BRAND EQUITY TERHADAP KEPUASAN NASABAH PADA PT. BANK SYARIAH MANDIRI KCP MEDAN AKSARA - Tetty Yuliaty (JURNAL ILMIAH MANAJEMEN & BISNIS, 2014)
This research aims to analyze the effect of internet banking quality service and brand equity to customer satisfaction in Bank Syariah Mandiri KCP Medan Aksara. Sample were 40 persons and the method used is accidental sampling. The data was collected by distributing questionnaires to the respondents. The analysis used is multiple linear regression, where Y is customer satisfaction variable, X1 is the quality service of Internet Banking and X2 is Brand equity. Hypothesis testing by t-test showed that brand equity variable influence of positive and significant effect on customer satisfaction. While the quality service of internet banking  variable influence of positive on customer satisfaction but not significant.  Adjusted R2 of 0,186 indicates that 18,6% customer satisfaction can be explained by quality service of internet banking variable and brand equity. While the rest 81,40 % can be explained by other variables outside of five variables independent (X1) used in this research